Lexicography in Action: The Traversal from Coinage and Iconicity to Iconisation - Moalla Masmoudi, Dorra (Lexikos, 2025)
This paper seeks to connect Lexicography and Critical Discourse Analysis (CDA) by highlighting that the critical potential of Lexicography lies in the coinage of dictionary entries, which can function as semiotic acts that aim to rally the readers around the sign-maker’s world view. To illustrate this, Got Israeled, a new entry in the crowdsourced Urban Dictionary added on 21 October 2023, is taken as an example. This entry is defined as the act of allowing someone to share something with you but this person claims the thing as his/her own and expels you. The entry has gone viral on social media and induced divergent attitudes. Its wide reach is due to its iconic nature and coinage during the war on Gaza. The entry has also been heavily resemiotised inside Urban Dictionary and its critical potential has gradually increased clearly recontextualizing the colonization of Palestine and the issue of Jewish settlements. 36 entries added between 21 October 2023 and 10 July 2024 are analyzed at three levels: coinage, iconicity and iconisation. The analysis draws upon Semiotic and Social Semiotic frameworks, which include DeSaussure’s (1916) sign system, the Social Semiotic principle of motivated sign (Kress 1993), and Peirce’s (1931) principles of hypo-iconicity. An SFL-based analysis exploiting subsystems within the ideational and interpersonal metafunctions is employed to explain the sign’s ’iconisation’ (Halliday and Matthiessen 2014, Kress and Van Leeuwen 1996/2021, Martin and White 2005). The investigation simultaneously highlights the critical potential of the sign and describes its transformation into a bonding icon rallying people around the writers’ world view (Stenglin 2008, 2012). Keywords: lexicography in action, coinage, iconicity, iconisation, Urban Dictionary, motivated sign